Maintaining the airway. Issue 10 (October 2019) - Sykes, Peter; Elliott, Lucy; Rowe, Matthew
Airway-related problems can present in primary care. As first-contact care providers, GPs may encounter a range of airway emergencies that require urgent intervention. Patients may have residual symptoms from procedures such as endotracheal intubation or require specialised airways such as a tracheostomy in the community. This article concentrates on two issues focusing on the adult patient population. First, we discuss emergency airway maintenance in accordance with basic life support. Second, we explore the care of patients living with specialised airways in the community from a physical, psychosocial and emergency perspective.